EVALUASI PROGRAM KARAKTER RESPECT, RESPONSIBILITY, RIGHTEOUSNESS DI SMP CANDLE TREE TANGERANG SELATAN - Edi Dwani Widyanti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the importance of character education in the elementary education system in Indonesia. In recent years, negative phenomena such as bullying, intolerance, and violence in the school environment have increased, indicating the need for the integration of character values ​​into the education curriculum. This study uses a descriptive method with a qualitative and quantitative approach, involving in-depth interviews with teachers, students, and parents in several elementary schools. The results of the study indicate that strengthening students' character not only improves their quality of life, but also builds good morals and a sense of responsibility as citizens. The character education program implemented, such as the values ​​of respect, responsibility, and righteousness, has proven effective in shaping positive behavior among students. The implementation of a curriculum that supports character education and adequate resource support is essential to achieve these goals. Positive interaction activities between teachers and students are also key factors in creating a conducive learning environment.